Mating and post-copulation behavior in the tea leafhopper, Empoasca onukii (Hemiptera: Cicadellidae) - Shan, Yao; Zhou, Xiao-Sen; Cai, Xiao-Ming; Luo, Zong-Xiu; Li, Zhao-Qun; Xiu, Chun-Li; Chen, Zong-Mao; Bian, Lei (Frontiers in Plant Science, 2023)
The tea leafhopper, Empoasca onukii, relies on substrate-borne vibrations for sexual communication and is mainly controlled with chemical pesticides, which poses risks to the environment and food safety. Based on previous studies, we conducted a series of behavioral assays by simultaneous observation of vibration signals and movement to investigate the mating and post-copulation behavior of tea leafhoppers. During mating, the activity of E. onukii was restricted to dawn and dusk and concentrated on the sixth or seventh mature leaf below the tea bud. By comparing the time spent in locating females among different males, the timely reply of females was the key factor affecting mating success. Empoasca onukii females mated only once in their lives, while males could mate multiple times. Male rivalry behavior involved two distinct strategies. The rivals could send disruptive pulses to overlap the male calling signals, locate the courting males, and drive them away after contact. Some rivals could emit mating disruption signals (MDSs) to interrupt the ongoing identification duet and establish their own mating communication. Both identification and location duets could be interrupted by playback of MDSs, which is essential to create effective synthetic signals to disrupt mating communication of E. onukii. Our study clarified the spatial and temporal distribution of E. onukii in mating and the function of MDSs, which will be essential to develop future vibrational mating disruption techniques for E. onukii and its energy-efficient application in the field.